Associations of Serum and Red Blood Cell Folate With All-Cause and Cardiovascular Mortality Among Hypertensive Patients With Elevated Homocysteine - Zhou, Long; Huang, Hui; Wen, Xiaoxiao; Chen, Yu; Liao, Jie; Chen, Fuli; Zhao, Liancheng; Liu, Mingjiang; Tao, Jianhong; Li, Gang (Frontiers in Nutrition, 2022)
Objectives This study aims to explore the association between serum and red blood cell (RBC) folate as indicators of short- and long-term folate status respectively, and all-cause as well as CVD mortality among hypertensive patients with elevated homocysteine. Methods A prospective cohort study of the National Health and Nutrition Examination Survey (1999-2006) and 2015 Linked Mortality File was performed. All-cause and CVD mortality risk estimated using Cox proportional hazards models with adjusting for multiple potential covariates. Results A total of 1753 hypertensive patients with elevated homocysteine (mean [SD] age, 68.5 [13.1]) were included in the analysis. During a median follow-up of 10.0 years, a total of 899 all-cause and 257 CVD deaths occurred. Compared the highest with the lowest quartile of RBC folate, the multivariable adjusted hazard ratios and 95% confidence intervals for all-cause and CVD death were 1.13 (0.92-1.39) and 1.47 (1.01-2.16) respectively. There was a significant and positive trend between RBC folate and the risk of CVD death (p for trend=0.0196). No significant association was found between serum folate and mortality risk among the study sample. Conclusions High level of RBC folate is associated with an increased risk of cardiovascular mortality among hypertensive patients with elevated homocysteine while serum folate has no such effects.